1998
DOI: 10.1099/00207713-48-4-1333
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella tribocorum sp. nov., a new Bartonella species isolated from the blood of wild rats

Abstract: Two Bartonella strains from blood of two wild rats (Rattus norvegicus) living in a rural environment were isolated. These strains were distinct from all previously known Bartonella species based on phenotypic and genotypic characteristics. This new species is distinguished by its trypsin-like activity, the absence of the ability to hydrolyse proline and tributyrin, its 165 rRNA and citrate synthase gene sequences and by whole-DNA hybridization data. This new species, for which the name Bartonella tribocorum sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 18 publications
5
97
0
3
Order By: Relevance
“…We infer that these mutations occurred among the different original isolates that are hypothetically attributed to the variants in host and geographic factors. B. tribocorum is a rodent-associated species that is distributed widely and that has been isolated from R. norvegicus in Europe and North America (Heller et al, 1998;Ellis et al, 1999). Ying et al (2002) demonstrated a B. tribocorum bacteremia in R. norvegicus and R. tanezumi flavipectus in western Yunnan, China.…”
Section: Discussionmentioning
confidence: 99%
“…We infer that these mutations occurred among the different original isolates that are hypothetically attributed to the variants in host and geographic factors. B. tribocorum is a rodent-associated species that is distributed widely and that has been isolated from R. norvegicus in Europe and North America (Heller et al, 1998;Ellis et al, 1999). Ying et al (2002) demonstrated a B. tribocorum bacteremia in R. norvegicus and R. tanezumi flavipectus in western Yunnan, China.…”
Section: Discussionmentioning
confidence: 99%
“…An approximately 1500 bp fragment of the 16S rRNA gene was amplified from the extracted DNA by using the eubacterial universal primers specific for the 16S rRNA gene, i.e. primer P8 (5h-AGAGATTTGATCCTGGCTCAG-3h) and primer Pc1544 (5h-AAGGAGGTGATCCAGCCGCA-3h) (Heller et al, 1998). PCR amplification of the citrate synthase gene was performed, as described by Birtles & Raoult (1996), with two primers, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The 12th approved species is Bartonella elizabethae (Daly et al, 1993), for which only a single isolate, originating from a human case of endocarditis, was described. The 16S rRNA gene sequence of this species is close to that of the rat Bartonella sp., B. tribocorum (Heller et al, 1998) and to that of other isolates not yet validly described, but all were isolated from small wild mammals (Birtles & Raoult, 1996 ;Kosoy et al, 1997). In addition to these 12 species, two others have been described in Peromyscus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been isolated from wild and domestic animals including cats, dogs, deer, cattle, and rodent, among others [7,11,20,24]. Because Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%